Evaluation of conservative treatment or osteosynthesis in the treatment of cats with metacarpal and/or metatarsal fractures: a retrospective study - Halil Caltiner; Iremsu Satici; Mustafa Arican (Eurasian Journal of Veterinary Sciences)
Aim: This study aims to assess the merits, drawbacks, and postoperative outcomes associated with conservative treatment and osteosynthesis methods employed in managing metacarpal (MC) and/or metatarsal (MT) bone fractures resulting from trauma in cats. Materials and Methods: The research encompassed a sample of fifty-two cats of varying breeds, genders, and ages, all presenting with metacarpal and/or metatarsal bone fractures between 2022 and 2023. Conservative treatment was administered in 46 cases, while osteosynthesis was applied in the remaining 6 cases. Results: In the group treated conservatively, 29 cases (63.04%) exhibited no signs of lameness at the 6-week examination, indicating a successful recovery with unimpeded mobility. In contrast, mild lameness was observed in the remaining cases (36.96%) at the 6-week check-up. Upon reassessment at the 12-month examination, 43 cases (93.47%) demonstrated unimpeded walking, with only 3 cases (6.53%) experiencing occasional mild lameness. Conversely, 2 cases (33.3%) showed a complication-free recovery among the cats undergoing osteosynthesis, while postoperative issues emerged in 4 cases (66.6%). In one complication-free case (50%), mild lameness was noted at the 6-week examination, and in the other case (50%), occasional mild lameness was observed. Importantly, all cases exhibited uneventful walking during the 12-month assessment. Conclusion: Conservative treatment proves to yield favorable outcomes in cats, both independently and when osteosynthesis applications fall short. However, the limited number of surgical cases examined in the study constrains the findings' generalizability.